Knowledge and Health-Related Quality of Life Link Assessment in Warfarin Patients: A Saudi Arabian Experience - Fahad Alsaikhan, (Asian Journal of Pharmaceutics (AJP), 2025)
Purpose: The aim of this study was to elaborate on warfarin therapy knowledge and health-related quality of life (HRQoL) association among Saudi Arabian warfarin-using patients. Methods: The study involved 387 warfarin patients from an outpatient anticoagulation clinic of the University Hospital in Al-kharj, Saudi Arabia. A self-developed and pre-validated questionnaire was used to assess warfarin therapy knowledge, whereas World Health Organization Quality of Life Brief Version (WHOQOL-BREF) was used to estimate HRQoL. Patients’ demographic characteristics and different variables’ correlations were established through descriptive and inferential statistics. Results: A total of 387 patients (Males = 130, 33.6% and Females = 257, 66.4%) participated in the study. The study population presented a mean knowledge score of 9.94 ± 2.48. Environment, social relationships, psychological, and physical health domains had mean HRQoL scores of 63.43 ± 17.60, 64.46 ± 26.19, 68.20 ± 16.11, and 62.11 ± 15.53, respectively. The correlation coefficients of these WHOQOLBREF domains were noted as −0.121, −0.112, −0.160, and −0.111 in relation to warfarin therapy knowledge total score, which indicated a weak negative association among these domains. Conclusion: The negative association between warfarin therapy knowledge and warfarin patients’ HRQoL indicates that warfarin therapy knowledge does not necessarily improve their HRQoL.